Programming Language Techniques for Cryptographic Proofs - Barthe, Gilles; Grégoire, Benjamin; Zanella-Béguelin, Santiago (1st International Conference on Interactive Theorem Proving, ITP 2010, 2010)
CertiCrypt is a general framework to certify the security of cryptographic primitives in the Coq proof assistant. CertiCrypt adopts the code-based paradigm, in which the statement of security, and the hypotheses under which it is proved, are expressed using probabilistic programs. It provides a set of programming language tools (observational equivalence, relational Hoare logic, semantics-preserving program transformations) to assist in constructing proofs. Earlier publications of CertiCrypt provide an overview of its architecture and main components, and describe its application to signature and encryption schemes. This paper describes programming language techniques that arise specifically in cryptographic proofs. The techniques have been developed to complete a formal proof of IND-CCA security of the OAEP padding scheme. In this paper, we illustrate their usefulness for showing the PRP/PRF Switching Lemma, a fundamental cryptographic result that bounds the probability of an adversary to distinguish a family of pseudorandom functions from a family of pseudorandom permutations.